Categorization of Project Complexity Factors In Malaysian Construction Industry - M., Abdou Saed; Yong, Kuan; Othman, Mohamed (International Journal of Property Sciences (E-ISSN: 2229-8568), 2017)
The disagreement on project complexity is a crucial problem as project complexity is closely related to the project management process particularly for the construction industry. Due to its negative influence on project management process, project complexity therefore needs to be understood and managed efficiently particularly in construction projects. The literature review uncovered the disagreement on project complexity varied interpretation in which analysis of its essential concepts was provided. The intention of this paper is to provide an understanding on the project complexity and its implications on the construction projects and to stimulate debate on this controversial topic. This paper intends to determine and categorise factors for project complexity influencing the construction projects in Malaysia. The data were collected through a survey of 101 respondents. The results indicated that, there are three categories of project complexity factors that influence the construction project in Malaysia. It is concluded that the project complexity concept is worthy to be studied further.